Physicochemical and Electrical Properties of Praseodymium Oxides - Sergio Ferro (International Journal of Electrochemistry)
The industrial research is continuously looking for novelties that could improve the applied processes, increasing the yields, lowering the costs, or improving the performances. In industrial electrochemistry, one more aspect is the stability of electrode materials, which is generally balanced by the catalytic activity: the higher the latter, the lower the former. A compromise has to be found, and an optimization is often the result of new ideas that completely change the way of thinking. Praseodymium-oxide-based cathodes have been proved to be quite interesting devices: the hydrogen evolution reaction is guaranteed by the presence of a noble metal (platinum and/or rhodium), while the stability and poisoning resistance seem to be strongly improved by the presence of lanthanide oxides.